UTILIZATION OF THE CAPCUT APPLICATION IN IMPROVING SPEAKING SKILLS FOR STUDENTS AT ISLAMIC BOARDING SCHOOLS - Amrina Amrina; Arif Mufti; Mariam Khan (Yayasan Adra Karima Hubbi, 2025)
The CapCut application has many impacts, both positive and negative. One of the positive impacts is being able to improve students' speaking skills while the negative impact is reducing students' potential in maharah kalam (speaking skills) and reducing students' mindset in learning Arabic. This is due to the lack of teacher knowledge of the material being taught. The purpose of this study is to Utilize the CapCut Application in Improving Speaking Skills for students at an Islamic Boarding School. This research method uses a Quantitative method, data collected through interviews and distributing questionnaires via Google forms. The results of the study indicate that the use of the CapCut application for speaking skills is more efficient, with easy-to-understand features in the application. From this study, it can be concluded that the CapCut application, which was originally developed for video editing, can also be used to improve students' speaking skills by creating presentation videos and adding interesting audio and visual effects. The limitation of this study is that the researcher only conducted research on the use of the CapCut application in improving speaking skills for students, whereas there are still many other media uses that can be used as alternatives in improving speaking skills. The researcher hopes that future researchers can conduct research related to improving speaking skills, but using other applications. This study also recommends that future researchers use this study as a reference for conducting research on students' speaking skills using the CapCut application at Islamic Boarding Schools.